Interaction between Saikosaponin D, Paeoniflorin, and Human Serum Albumin - Liang, Guo-Wu; Chen, Yi-Cun; Wang, Yi; Wang, Hong-Mei; Pan, Xiang-Yu; Chen, Pei-Hong; Niu, Qing-Xia (Molecules (Basel, Switzerland), 2018)
Saikosaponin D (SSD) and paeoniflorin (PF) are the major active constituents of Bupleuri Radix and Paeonia lactiflora Pall, respectively, and have been widely used in China to treat liver and other diseases for many centuries. We explored the binding of SSD/PF to human serum albumin (HSA) by using fluorospectrophotometry, circular dichroism (CD) and molecular docking. Both SSD and PF produced a conformational change in HSA. Fluorescence quenching was accompanied by a blue shift in the fluorescence spectra. Co-binding of PF and SSD also induced quenching and a conformational change in HSA. The Stern-Volmer equation showed that quenching was dominated by static quenching. The binding constant for ternary interaction was below that for binary interaction. Site-competitive experiments demonstrated that SSD/PF bound to site I (subdomain IIA) and site II (subdomain IIIA) in HSA. Analysis of thermodynamic parameters indicated that hydrogen bonding and van der Waals forces were mostly responsible for the binary association. Also, there was energy transfer upon binary interaction. Molecular docking supported the experimental findings in conformation, binding sites and binding forces.